Production Of Wood Products At The Suka Bersama Factory In Melayu Ulu Village, Banjar District - Yeti Novita Purnama Sari; Syaharuddin Syaharuddin; M. Ridha Ilhami; Sigit Triyono; Sovia Husni Rahmia (The Innovation of Social Studies Journal, 2025)
Suka Bersama Factory, located in Melayu Ulu Village, Banjar Regency, is one of the factories that process timber to make timber beam products as building materials. Along with the times and changing consumption patterns, more and more buildings are switching to using modern building materials such as concrete and steel, which reduces the use of wood in construction. This affects the sustainability of the wood processing industry, which needs to respond to the challenge of environmental sustainability. In this context, this study aims to understand how timber production is carried out at Suka Bersama Factory as well as the factors that influence production such as, capital, raw materials, machinery and equipment as well as the existing workforce at Suka Bersama Factory. The research method used is descriptive with a qualitative approach, which collects data through direct observation, interviews, and documentation. This research focuses on how timber production at the factory is carried out by timber production factors, such as capital, the use of raw materials sourced from sustainably managed forests, machinery and equipment, and labor. The results show that the timber production of Suka Bersama Factory is carried out systematically starting from the selection of raw materials for logs, processing using win machines, to the preparation of cooked goods or packaging of the final product. This process involves several important stages, namely the preparation stage, the processing stage, and the packaging stage.